Revolutionary movements in Africa : an untold story - Bianchini, Pascal; Sylla, Ndongo Samba; Zeilig, Leo (Pluto Press, 2024)
While the revolutionary leftist movements of the 1960s and'70s in Europe, the United States and Latin America have been the subject of abundant literature, similar movements that emerged in Africa have received comparatively very little attention. This book sheds new light on these political movements. Africa's left were extremely active in these years. With pro-Soviet movements, Maoism, Trotskyism, Guevarism, Pan-Africanism and the Black Panthers, the rumble of revolution was felt across the continent. From feminist student rebels in Nigeria to pro-democracy moments in Liberia, the exciting and complex interplay between these many actors changed Africa forever. Can we see echoes of these movements in African politics today? What can we learn from the people who lived through these decades? This unique collection will open the eyes of leftists across the world who will find new and important insights into an important chapter in global history.
Keywords: Revolutions -- Africa.; Africa -- Politics and government.; Révolutions -- Afrique.; Afrique -- Politique et gouvernement.; Politics and government; Revolutions; Africa